Design and implementation of campus social blogging culture circle based on multi-end convergence - Song, Jiayin; Shi, Xue (Transactions on Computer Science and Intelligent Systems Research, 2025)
In the context of the deep penetration of the mobile Internet into campus life, in response to the problems of traditional campus communities such as scattered functions, information silos, and insufficient interactivity, this study takes Dalian Maritime University as a pilot, and designs and implements the ‘Ocean Wave Bay’ multi-terminal interconnected campus social blogging and culture circle platform, which adopts multi-terminal convergence architecture, covering WeChat The platform adopts a multi-converged architecture, covering WeChat, applets, web pages and background management system, and adopts SpringBoot, WeChat applets, vue and other technology stacks to build the system, adopts a layered architecture and a hybrid storage mode to integrate AI intelligent recommendation, blockchain depository function, covering the three core modules of cultural dissemination, community interaction, and service integration. The core requirements of users (students, teachers, administrators) are clarified through demand analysis, and tests and pilot applications show that the average daily activity of platform users reaches 35%, the efficiency of campus activities organisation is improved by 91.7%, and user satisfaction reaches 82%, which effectively solves the pain points of traditional campus platforms.
Keywords: Campus Social; Multi-End Convergence; Intelligent Recommendations; Digital Platforms.